If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(15) = y Multiply 8 * 15 120 = y Solving 120 = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 120 + -1y = y + -1y Combine like terms: y + -1y = 0 120 + -1y = 0 Add '-120' to each side of the equation. 120 + -120 + -1y = 0 + -120 Combine like terms: 120 + -120 = 0 0 + -1y = 0 + -120 -1y = 0 + -120 Combine like terms: 0 + -120 = -120 -1y = -120 Divide each side by '-1'. y = 120 Simplifying y = 120
| 7+2t-4=8t+11-5t | | 2x-15=5x | | 6x+2=4x+12 | | 4x+63=14x-7 | | -3(x+5)=-27 | | 9x+17=5x+13 | | 6(2x+3)=66 | | 3(m-4)+2(5+2m)=29 | | 5+7y=2x+7+6y | | 16x+12=8x+41 | | 6x=3x+3 | | 9x+6=-57 | | r^3-3r+2=0 | | y=3(1)-10 | | 3x-10=2x-5 | | P(x)=x^3+7x^2+4x | | m^6-16m^3+64=0 | | 6x+3=6(4)+3 | | .50(6-y)=y | | -10.2x=71.4 | | 4x^2-33x+41=-9x+6 | | 6t=-46 | | 5x-9=4(x-3) | | 5p=-15 | | -9(2b+3)+(19b-3)=0 | | 7y^2-8y+15-11y^2-8y+6= | | a^2+8a=9 | | x=-11 | | -(3x+5)+1-4(x-2)+5x-2=0 | | x^2-2x+4=8x-4 | | t^2-10t-24=0 | | x^2+12x+6=0 |